Management accounting and cost analysis - Bezverkhnya, Yuliia; Безверхня, Юлія Вікторівна; Безверхняя, Юлия Викторовна (My University, 2020)
Modern management accounting of production costs is organized by their economic elements, and accounting and costing of individual types of products, works and services is carried out by expenditure items. The economic element is a homogeneous type of cost that cannot be decomposed into any component parts. According to the economic elements creates an estimate of the cost. Among them, there are five main elements: material costs, labor costs, social contributions, depreciation of fixed assets, and other costs.
Keywords: management accounting; costs; cost analysis